STATUS GIZI ANAK BERHUBUNGAN DENGAN COGNITIVE DAN BEHAVIOUR SESUAI DENVER DEVELOPMENTAL SCREENING TEST - Festy Ladyani Mustofa; Arti Febriyani Hutasuhut; Ajeng Larasati (JKM (Jurnal Kebidanan Malahayati), 2021)
RELATIONSHIP OF CHILDREN’S NUTRITIONAL STASTUS WITH COGNITIVE AND BEHAVIOURS ACCORDING TO DENVER DEVELOPMENTAL SCREENING TEST  Background:One of the important factors that affect child development is nutrition. Lampung Province has a percentage of malnutrition of 1.6%, malnutrition of 12.4%. The results of the 2013 Riskesdas showed the prevalence of under-five nutritional status (BW / U) in Bandar Lampung City for 3.5% malnutrition, 12.3% under nutrition, 78.2% good nutrition and 5.9% over nutrition. Poor nutritional status in toddlers can have an effect that greatly hinders their physical, mental and thinking abilities which in turn will reduce the work ability of toddlers in their activities.Puprose of this study was to determine the relationship between children's nutritional status with cognitive and behavior according to the Denver Developmental Screening Test at TK An-Nur Sumber Rejo Kemiling, Bandar Lampung City in 2020. Methods The study used the Denver Developmental screening Test as a research instrument. The population in this study were students who attended Kindergarten An-Nur Sumber Rejo Kemiling, Bandar Lampung City. The sample in this study was a total population of 57 students. Researchers used data collection techniques or measuring instruments using the Denver Developmental Screening Test. Analysis of the relationship using the chi square test. Result The frequency distribution of respondents with normal nutritional status was 40 respondents (70.2%), respondents with normal cognitive and behavioral development were 36 respondents (63.2%). There is a relationship between children's nutritional status and cognitive and behavior according to the Denver Developmental Screening Test at Kindergarten An-Nur Sumber Rejo Kemiling, Bandar Lampung City in 2020 (p value 0.011). Conclusion there is a relationship between children's nutritional status and cognitive and behavior.Suggestion can improve Maternal and Children Health (MCH) services as well as services for infants under five to prevent the occurrence of malnutrition. In addition, early detection services for growth and development must be carried out more thoroughly Keywords: Child Nutritional Status, Cognitive and Behavior ABSTRAK Latar Belakang Salah satu faktor penting yang mempengaruhi tumbuh kembang anak adalah faktor gizi. Provinsi Lampung memeliki persentase gizi buruk sebesar 1,6%, gizi kurang sebesar 12,4%.  Hasil Riskesdas tahun 2013 menunjukkan Prevalensi status gizi balita (BB/U) di Kota Bandar Lampung untuk gizi buruk 3.5%, gizi kurang 12.3%, gizi baik  78.2% dan gizi lebih 5.9%.Status gizi yang buruk pada balita dapat menimbulkan pengaruh yang sangat menghambat fisik, mental maupun kemampuan berfikir yang pada akhirnya akan menurunkan kemampuan kerja balita dalam aktivitasnya.Tujuan penelitian ini untuk mengetahui hubungan status gizi anak dengan cognitive dan behaviour sesuai Denver Developmental Screening Test di TK An-Nur Sumber Rejo Kemiling Kota Bandar Lampung tahun 2020.Metode penelitian kuantitatif dengan pendekatan cross sectional. Populasi murid yang bersekolah di TK An-Nur Sumber Rejo Kemiling Kota Bandar Lampung, Sampel total populasi sejumlah 57 siswa. Peneliti menggunakan teknik pengumpulan data atau alat ukur dengan menggunakan Denver Developmental Screening Test. Analisis hubungan menggunakan uji chi square.Hasil Penelitian menunjukkan distribusi frekuensi responden dengan status gizi normal, yaitu sebanyak 40 responden (70,2%), responden dengan Perkembangan Cognitive Dan Behaviour normal, yaitu sebanyak 36 responden (63,2%). Ada hubungan status gizi anak dengan cognitive dan behaviour sesuai Denver Developmental Screening Test di TK An-Nur Sumber Rejo Kemiling Kota Bandar Lampung Tahun 2020 (p value 0,011).Kesimpulan Ada hubungan status gizi anak dengan cognitive dan behaviour.Saran dapat meningkatkan pelayanan kesehatan ibu dan anak (KIA) serta pelayanan bayi balita untuk mencegah terjadinya kejadian gizi kurang. Selain itu pelayanan deteksi dini tumbuh kembang harus dilakukan dengan lebih teliti Kata Kunci : Status Gizi Anak, Cognitive Dan Behaviour